(8x-9=6x-7)

Simple and best practice solution for (8x-9=6x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8x-9=6x-7) equation:



(8x-9=6x-7)
We move all terms to the left:
(8x-9-(6x-7))=0
We calculate terms in parentheses: +(8x-9-(6x-7)), so:
8x-9-(6x-7)
determiningTheFunctionDomain 8x-(6x-7)-9
We get rid of parentheses
8x-6x+7-9
We add all the numbers together, and all the variables
2x-2
Back to the equation:
+(2x-2)
We get rid of parentheses
2x-2=0
We move all terms containing x to the left, all other terms to the right
2x=2
x=2/2
x=1

See similar equations:

| x—5=8—2(x+2) | | 10(s-9)=197 | | 10x—18=3+8x | | 136=8(-1+4x) | | Y=2x²-12x+16 | | O=2x²-12x+16 | | F(x)=2x^2-15x+7 | | 25x+20x=420 | | 4-2c=10-8c= | | 2y/9=2 | | (3-8c)1.5=4.5-12c | | (8x+19=59) | | (9x+2=7x+18) | | 20=-4.9x^2-42x+100 | | x*2x=392 | | x+x+42=300 | | Z^4+13z^2+36=0اعدادمركبه | | (5x+19=6x+1) | | (7x+3=8x+1) | | (6x-8=5x+14) | | (5x+2=4x+6) | | 27+3x=x+93 | | B(40)=15.00-0.09x | | k=49÷7 | | 22-6x=4x16 | | 3h+10=37 | | 8(2x+5)=88 | | 124x-7=53 | | 4(x–5)+10=30 | | 4(b–5)+10=30 | | xx4+102=xx7+15 | | 5*28-x+72=172 |

Equations solver categories